2021
DOI: 10.1002/eap.2389
|View full text |Cite
|
Sign up to set email alerts
|

Consistent declines in aquatic biodiversity across diverse domains of life in rivers impacted by surface coal mining

Abstract: The rivers of Appalachia (United States) are among the most biologically diverse freshwater ecosystems in the temperate zone and are home to numerous endemic aquatic organisms. Throughout the Central Appalachian ecoregion, extensive surface coal mines generate alkaline mine drainage that raises the pH, salinity, and trace element concentrations in downstream waters. Previous regional assessments have found significant declines in stream macroinvertebrate and fish communities after draining these mined areas. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…However, a holistic view of ecosystems is urgently needed to comprehend the whole myriad of impacts and potential consequences incurred on ecosystem processes and functions. By examining eDNA from streams impacted by mountaintop coal mining in Central Appalachia, USA, Simonin et al (2021) found, even at low mining levels, synchronous declines in aquatic biodiversity across domains of life, thus suggesting that current regulations provide insufficient environmental protection. Such pan‐ecosystem eDNA biomonitoring would enable comprehensive assessments of anthropogenic environmental impacts and facilitate ecosystem‐scale management for effective mitigation.…”
Section: New Frontiers In Fish Edna Researchmentioning
confidence: 99%
“…However, a holistic view of ecosystems is urgently needed to comprehend the whole myriad of impacts and potential consequences incurred on ecosystem processes and functions. By examining eDNA from streams impacted by mountaintop coal mining in Central Appalachia, USA, Simonin et al (2021) found, even at low mining levels, synchronous declines in aquatic biodiversity across domains of life, thus suggesting that current regulations provide insufficient environmental protection. Such pan‐ecosystem eDNA biomonitoring would enable comprehensive assessments of anthropogenic environmental impacts and facilitate ecosystem‐scale management for effective mitigation.…”
Section: New Frontiers In Fish Edna Researchmentioning
confidence: 99%
“…Consequently, biodiversity surveys commonly do not include chemical analytics but tend to rely on other indicators of environmental quality instead, even in cases where biodiversity changes are likely to be directly influenced by chemical pollutants. For example, in a recent study that documented an up to 40% biodiversity loss in streams affected by mining activity, the observed biodiversity patterns were correlated to water conductivity . While a useful initial indicator of water quality, this parameter does not inform on the accompanying risk factors, such as exposure to heavy metals or other contaminants leaching from mining sites.…”
Section: Biodiversity Research Should Make Use Of Environmental Toxic...mentioning
confidence: 99%
“…The environmental risks of coal mine drainage on aquatic biodiversity have been documented in numerous cases (e.g. (Simonin et al, 2021). Land use change related to mining activities such as mountain top removal may be devastating for the affected ecosystems.…”
Section: Greenhouse Gases -Root Cause or Symptom?mentioning
confidence: 99%